Pharmacological Screening For Analgesic And Anti Inflammatory Activities Of Eriolaena Hookeriana Wt. & Arn. Roots - K. GNANANATH; A. SANJEEVA KUMAR; N. SRINIVAS; P. GOMATHI; K. KISHORE KUMAR (International Journal of Pharma and Bio Sciences, 2012)
Eriolaena hookeriana is widely distributed in Central and southern India and is available in all parts of Andhra Pradesh. In present study, the roots of Eriolaena hookeriana were extracted by successive solvent extraction using Methanol and Water as solvents and the extracts were screened for anti inflammatory and analgesic activities on laboratory animals. Anti inflammatory activity was measured using carrageenan induced paw edema model and analgesic activity was measured by Tail immersion method and Acetic acid-induced writhing methods. Diclofenac sodium was used as standard for both the activities. Analgesic and anti-inflammatory activities showed by both the extracts significantly at the 100 mg/kg and 250 mg/kg dose levels. AQEH extract showed significant activity when compared to that of ALEH. The root extracts of E. hookeriana possesses potent anti-inflammatory and moderate analgesic properties